Estimation of the damping derivative in pitch for a wedge at supersonic Mach numbers using design of experiments - Shaikh, Javed Shoukat; Kumar, Krishna; Pathan, Khizar Ahmed; Khan, Sher Afghan; Husain, Kharadi Fayaz; Siddiqui, Afreen (Akademia Baru Publishing (M) Sdn Bhd, 2025)
This work primarily focuses on numerically modeling the damping derivative over the 2D wedge at different pivot points for considerable values of Mach number and incidence angles. The damping derivative is numerically simulated using regression model analysis. The two-dimensional piston theory of Ghosh is applied to obtain the analytical findings. The current study considers the variables Mach number, wedge angle, and pivot location. In the present investigation, the wedge angle (θ) varies between 2° and 20°, while the Mach number (M) spans 2.2 to 4.0. The results of the damping derivatives are derived by analyzing different Mach numbers (M) and angles of incidence (θ) at various pivot positions (h) ranging from 0.0 to 1.0. This study evaluates the damping derivative results against theoretical predictions, revealing a significant alignment between the two. Both the research findings and the theoretical forecasts show a striking similarity. This research demonstrates that the variation in the damping derivative is influenced by factors like the Mach number (M), wedge angle (θ), and pivot position (h). At each pivot position, the magnitude of the damping derivative decreases with a rise in Mach number, which increases as the angle of incidence increases.